Understanding Student Investment Intentions: The Role of Inflation Expectations, Financial Literacy, and Trust in Digital Platforms on Mutual Fund Choices in Purwokerto - Vania Lardes Siregar; Rakhmat Priyono; Indrawan Firdauzi (Diponegoro Journal of Economics, 2025)
This study aims to analyze the influence of inflation expectations, income, financial literacy, and trust in digital platforms on mutual fund investment decisions among university students in Purwokerto. The gap between the number of productive-age individuals and mutual fund investors indicates that students' investment interest remains low despite the increasing accessibility of digital investment platforms. The research employs a quantitative approach using a survey method through questionnaires and multiple linear regression analysis. The sample was determined using purposive sampling, consisting of university students in Purwokerto who have invested or are currently investing in mutual funds. The results show that all independent variables simultaneously have a significant effect on mutual fund investment decisions. Partially, income, financial literacy, and trust in digital platforms have a positive and significant effect. In contrast, inflation expectations have no significant effect. These findings indicate that students' investment decisions are more strongly influenced by financial capacity, financial knowledge, and trust in digital platforms rather than macroeconomic factors such as inflation. As a novel contribution, this paper provides a new contribution by integrating macroeconomic information and psychosocial factors into the student investment behavior model, which has so far been limitedly studied in the context of young investors in educational hub regions such as Purwokerto.